FARMING ANALYSIS OF GRASS ODOT (Pennisetum purpureum cv. Mott) in VILLAGE OF MEDOWO, SUB DISTRICT OF KANDANGAN, DITRICT OF KEDIRI - Wicaksono, Anggit Putra; Ibrahim, Jabal Tarik; Bakhtiar, Ary (AGRIBEST, 2019)
The problem of forage limitations experienced by farmers as well as dairy farmers in Medowo Village, Kandangan District, Kediri when the dry season arrives. Farmers take other forage alternatives that can grow in all seasons and have more nutritional content than other forages. namely odot grass (Pennisetum Purpureum Cv.Mott). The purpose of this study is 1) to analyze the production costs of odot grass farming, revenue and income of odot grass farming, and 2) analyze the R / C Ratio of odot grass farming. This research was conducted in Village  of Medowo, Sub-District of Kandangan, District of Kediri and the sampling method used was simple random sampling technique with a number of respondents as many as 50 farmers. Data analysis technique used is the calculation of farming and production costs, with quantitative descriptive data analysis methods. The results of this study found an average total fixed cost that is equal to IDR 6,039,302 / ha, the total average variable cost is IDR.11,055,632.8 / ha, the average total production cost is IDR.17,095,270, 1 / ha, the total average revenue is IDR 31,479,403.81 / ha, while the average income received is IDR 2,720,370 / ha. The efficiency results (R / C Ratio) of 1.8 or worth the effort.